2020
DOI: 10.1186/s13058-020-01363-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from young women’s breast cancer patients drive increased invasion of non-malignant cells via the Focal Adhesion Kinase pathway: a proteomic approach

Abstract: Background Extracellular vesicles (EVs) are small membrane particles that contribute to cancer progression and metastases by transporting biologically significant proteins and nucleic acids. They may also serve as biomarkers of various disease states or important therapeutic targets. Breast cancer EVs have the potential to change the behavior of other cells in their microenvironment. However, the proteomic content of EVs isolated from young women’s breast cancer patients and the mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 85 publications
0
21
0
1
Order By: Relevance
“…EVs are sensory molecules for information exchange between tumor cells in the microenvironment, activating different signaling pathways and influencing the development, progression and metastasis of tumors ( 294 297 ). In recent years, EVs have become promising vehicles in liver disease for their low toxicity, high stability and preferential absorption ( 298 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs are sensory molecules for information exchange between tumor cells in the microenvironment, activating different signaling pathways and influencing the development, progression and metastasis of tumors ( 294 297 ). In recent years, EVs have become promising vehicles in liver disease for their low toxicity, high stability and preferential absorption ( 298 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that many upregulated genes in BCYW that are also upregulated in normal breast tissues encode proteins secreted in EVs or body fluids such as urine, saliva, breast milk, and plasma is important as it raises the possibility of developing non-invasive predictive biomarkers for the general screening of younger women who are currently excluded from the guidelines to use mammography and/or individuals without predisposed breast cancer genes. Following a somewhat similar line of thinking, but in the context of prognosis, a recent study suggested differences in the nature of cargo EVs purified from the plasma of young BC patients as compared to those from healthy donors [ 76 ]. As a good percentage of breast cancers in young women are of the TNBC subtype, it would be important to understand the nature of biomaterial packed within the circulating EVs from different subtypes of BCYW.…”
Section: Discussionmentioning
confidence: 99%
“…EVs are released from all cell types studied to date, including endothelial cells [ 7 , 8 ], epithelial cells [ 9 ] and mesenchymal stem cells [ 10 , 11 ]; hence, they can also be found in a number of biofluids, including blood [ 12 ], synovial fluid [ 13 ], bile [ 14 ], breast milk [ 15 ], cerebrospinal fluid [ 16 ] and urine [ 17 ]. EVs have also been implicated in a number of diseases, including cardiovascular [ 18 , 19 , 20 ] and liver diseases [ 21 , 22 ], autoimmune [ 23 ] and neurodegenerative conditions [ 24 , 25 , 26 ] and cancer [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%